2017
DOI: 10.1038/ncomms16105
|View full text |Cite
|
Sign up to set email alerts
|

Long-term microdystrophin gene therapy is effective in a canine model of Duchenne muscular dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is an incurable X-linked muscle-wasting disease caused by mutations in the dystrophin gene. Gene therapy using highly functional microdystrophin genes and recombinant adeno-associated virus (rAAV) vectors is an attractive strategy to treat DMD. Here we show that locoregional and systemic delivery of a rAAV2/8 vector expressing a canine microdystrophin (cMD1) is effective in restoring dystrophin expression and stabilizing clinical symptoms in studies performed on a total of 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
173
3
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(190 citation statements)
references
References 61 publications
5
173
3
9
Order By: Relevance
“…In the past years, treatment breakthroughs have been made in small and large animal models of NMDs (Bengtsson, Hall et al, 2017a, Bengtsson, Hall et al, 2017b, Childers, Joubert et al, 2014, Le Guiner, Servais et al, 2017, Malerba, Klein et al, 2017, Pozsgai, Griffin et al, 2017 and clinical benefits have been reported after a single injection of recombinant adeno-associated virus (rAAV) in patients with spinal muscular atrophy (Mendell, Al-Zaidy et al, 2017). In most of these studies, results consist of correlations between transgene expression levels and clinical outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, treatment breakthroughs have been made in small and large animal models of NMDs (Bengtsson, Hall et al, 2017a, Bengtsson, Hall et al, 2017b, Childers, Joubert et al, 2014, Le Guiner, Servais et al, 2017, Malerba, Klein et al, 2017, Pozsgai, Griffin et al, 2017 and clinical benefits have been reported after a single injection of recombinant adeno-associated virus (rAAV) in patients with spinal muscular atrophy (Mendell, Al-Zaidy et al, 2017). In most of these studies, results consist of correlations between transgene expression levels and clinical outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…However, a gradual loss of dystrophin-positive myofibers was seen during a 5-year follow up (220,222). Furthermore, the new study showed that limb perfusion of the U7snRNA AAV8 vectors did not induce the T cell response to newly synthesized dystrophin nor to AAV capsid (207). Cardiac rescue is attained with U7snRNA AAV6 vectors by percutaneous transendocardial delivery in the GRMD dog heart (219,221).…”
Section: Therapeutic Testing In the Canine Model And Impact On Patienmentioning
confidence: 89%
“…Micro-dystrophin also improved growth, increased limb muscle force, and enhanced activity and gait. Collectively, preclinical studies in the canine model have provided compelling supporting data for conducting systemic AAV micro-dystrophin therapy in human patients (204)(205)(206)(207)(208). Three independent clinical trials (conducted by Solid Bioscience, Pfizer, and Sarepta) are currently ongoing (209).…”
Section: Therapeutic Testing In the Canine Model And Impact On Patienmentioning
confidence: 99%
“…Pioneering translational research in the gene therapy and immunotherapy fields was conducted in dogs with hemophilia B , Duchenne muscular dystrophy and cancer , respectively. Such pioneering projects in dog models have accelerated the development of groundbreaking novel therapeutics for the parallel human disease .…”
Section: Current State Of Regenerative Medicine Research In Dogsmentioning
confidence: 99%